Investigation of the adsorption-reduction mechanisms of hexavalent chromium by ramie biochars of different pyrolytic temperatures. (October 2016) - Zhou, Lu; Liu, Yunguo; Liu, Shaobo; Yin, Yicheng; Zeng, Guangming; Tan, Xiaofei; Hu, Xi; Hu, Xinjiang; Jiang, Luhua; Ding, Yang; Liu, Shaoheng; Huang, Xixian
Highlights: Ramie residue can be converted into biochar as an effective sorbent for Cr(VI) removal. Cr(VI) sorption on the biochars was dependent on their physiochemical properties resulting from pyrolysis temperature. Both electrostatic and ionic interactions were responsible for Cr(VI) adsorption and reduction. The low-temperature biochar had better adsorption capability due to its abundant carboxyl and hydroxyl groups. Abstract: To investigate the relationship between Cr(VI) adsorption mechanisms and physio-chemical properties of biochar, ramie residues were oxygen-limited pyrolyzed under temperature varying from 300 to 600 °C. Batch adsorption experiments indicated that higher pyrolysis temperature limits Cr(VI) sorption in terms of capacity and affinity due to a higher aromatic structure and fewer polar functional groups in biochar. Both electrostatic (physical) and ionic (chemical) interactions were involved in the Cr(VI) removal. For low-temperature biochar, the simple physical adsorption was limited and the significant improvement in Cr(VI) sorption was attributed to abundant carboxyl and hydroxyl groups. The adsorption-reduction mechanisms could be concluded that Cr(VI) ions were electrostatically attracted by the positively charged biochar surface and reduced to Cr(III), and then the converted Cr(III) was retained or discharged into the solution. The study demonstrates ramie residues can be converted into biochar as a low-cost and effective sorbent for Cr(VI) removal.